Modified quality loss for the analysis of product quality characteristics considering maintenance cost. Issue 3 (4th May 2022) - Jin, Kai; Liu, Xintian; Liu, Miao; Qian, Kangfeng
ABSTRACT: In view of the fact that the product cannot be restored to new for the actual maintenance, and the degradation rate gradually increases after the maintenance. A concept, quality characteristics of products should obey a multi-stage linear variation during service life, is proposed, which can be used to modify the quality loss model. The correlation among maintenance cost, quality loss, and the range of key quality characteristics (KQC) of product is considered, products' preventive maintenance (PM) schedules are further adjusted to obtain the optimal range of KQC. Failure data of the air bearing of the air conditioner and the piston are used as examples. This paper compares and analyzes the best preventive maintenance of in-service equipment from two dimensions of quality loss and maintenance cost. The results show that the optimal preventive maintenance range can reduce the total operating cost of enterprises. Scientific evaluation of the service life of in-service products, reasonable arrangement of product maintenance and decommissioning work, improved product utilization, and provided a new perspective for product quality research in the whole life cycle.